Evaluation of root and canal morphology of mandibular molar teeth by cone beam computed tomography: cross-sectional study - Rümeysa Şendişçi Gök; Hümeyra Tercanlı; Ali Ekinci (BMC Oral Health)
Abstract Objectives The objective of the research was to analyze the differences in root structure found in mandibular molars through cone beam computed tomography (CBCT) and to highlight their morphological features. Materials and methods This study retrospectively examined CBCT images of 200 patients, encompassing a total of 496 molars in the study group. The frequency of radix entomolaris (RE), radix paramolaris (RP), and C-shaped canals was assessed based on molar type, side, and gender. The data are presented as frequencies and percentages, and the Chi-square test was employed to analyze potential differences between groups. A significance level of p < 0.05 was set for all tests. The normality of the data was assessed using the Shapiro-Wilk test. Results The study included 91 males (47%) and 109 females (53%), with a mean age of 32.49 ± 14.29 years. The frequency of RE was 4.2% (n = 21), RP was 0.8% (n = 4) and C-shaped canal was 7.1% (n = 35) in 496 molars (first molars n = 247, second molars n = 249). RE, RP and C-shaped canal were found in 3.4%, 0.2% and 0.2% of the mandibular first molars, respectively; RE, RP and C-shaped canal were found in 0.8%, 0.6% and 6.8% of the second molars, respectively. There was no statistically significant difference between the root variations examined and gender and lateralisation (p > 0.05). Conclusions Identifying anatomical variations in mandibular molars holds clinical importance, as it can improve endodontic treatment outcomes and provide insight into existing failures. Early detection of C-shaped canals and additional root structures can provide more effective cleaning and disinfection processes by more customizing treatment plans.